Developing a fully 3d animated educational application to teach bifurcation lesion treatment. (25th November 2020) - Kini, A; Vengrenyuk, A; Bhatheja, S; Chamaria, S; Barman, N; Krishnamoorthy, P; Sharma, S
Abstract: Background: Coronary bifurcation lesions make up around 15 to 20 percent of interventions. Especially for younger interventionalists, they pose a steep difficulty curve due to the daunting set of ways treatment can diverge from the initial plan based on plaque shift or other complications. Purpose: BifurcAID 3D was designed to intuitively show some of the key phenomena during bifurcation lesion treatment. Plaque shift, the importance of proximal optimization, the opening of a jailed side branch, and the overlapping layers of stent in the Culotte technique are among some of the aspects of bifurcation lesion treatment that can benefit from a clear visual format. Methods: Iterating on the bifurcation algorithm developed at a high volume metropolitan PCI center, this fully animated application has many branching points where plaque shift is assessed and the treatment plan and animation varies accordingly to show reactive balloon angioplasty, stenting, or entirely switching to dedicated two stent techniques. Results: The resulting application is an easy-to-navigate algorithm for left and non left main bifurcation lesion treatment with fully animated clear depictions of bifurcation lesion treatments including provisional, bail-out strategies, and dedicated two stent techniques alongside descriptive text. Conclusions: Creating free educational content for aspiring and current physicians serves to elevate the field and lower the barriers to entry. BifurcAID 3D will make available intuitive education on complex bifurcation lesion treatment worldwide. Funding Acknowledgement: Type of funding source: Private grant(s) and/or Sponsorship. Main funding source(s): Abbott Vascular Education Grant